2013
DOI: 10.1287/orsc.1120.0802
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Integration in the Face of Specialization: How Firms Navigated the Winds of Disintegration and Shaped the Architecture of the Semiconductor Industry

Abstract: Although the stylized model of industry evolution suggests that firms transform from vertical integration to specialization over time, many industries still exhibit a continued persistence of integrated firms. In exploring this puzzle, I draw on detailed firm-level data from the semiconductor industry to analyze how integrated incumbents, beyond shifting to the specialized mode, reconfigured in the face of industry's vertical disintegration so as to coexist with the specialized firms. I propose and find that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 92 publications
4
69
0
Order By: Relevance
“…In contrast to these start-ups, large firms competing in the CPU and memory markets tended not to vertically disintegrate because complementarities between design and manufacturing provided keys to their competitive advantage 24 . These integrated device manufacturers were more likely to patent 'systemic innovations' than their vertically disintegrated peers 26 , and they also drove the process innovations that spilled over to the rest of the industry through the industry's collaborative research institutions 27 . Throughout this period, increasing development costs, shortening product cycles, and growing domestic and foreign competition limited the ability of firms to capture the social and private returns from their R&D investments 28 .…”
Section: Nature Electronicsmentioning
confidence: 99%
“…In contrast to these start-ups, large firms competing in the CPU and memory markets tended not to vertically disintegrate because complementarities between design and manufacturing provided keys to their competitive advantage 24 . These integrated device manufacturers were more likely to patent 'systemic innovations' than their vertically disintegrated peers 26 , and they also drove the process innovations that spilled over to the rest of the industry through the industry's collaborative research institutions 27 . Throughout this period, increasing development costs, shortening product cycles, and growing domestic and foreign competition limited the ability of firms to capture the social and private returns from their R&D investments 28 .…”
Section: Nature Electronicsmentioning
confidence: 99%
“…Recent empirical studies have found such results for the semiconductor industry (Strojwas, 2005;Kapoor, 2012) and the electronics sector in general (Luo, 2010, pp. 114-5;Luo et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 85%
“…Incumbents may rationally remain vertically-integrated by capitalizing on their integrative or combinative capabilities by introducing systemic innovations from recombining or integrating existing technology and process components (Teece, 1996;Helfat and Campo-Rembado, 2010;Kapoor, 2012). While remaining vertically-integrated, the incumbents may further improve the efficiency of their internal units by allowing them to directly transact with and/or compete with specialized firms in the intermediate markets (Jacobides and Billinger, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As an illustrative example, consider Advanced Micro Devices Inc. (AMD) and National Semiconductor Corporation (NSC) during 1977-1999. 4 Both firms operated mainly in the semiconductors subsector of the high tech information technology industry, a setting that has historically experienced great variation in the level of technological uncertainty, the cost of residual technological uncertainty, and the cost of alliances (e.g., Bresnahan and Greenstein 1999;Frankort 2013;Grove 1996;Kapoor 2013;Schilling 2015;Sytch et al 2011), and so we might expect a priori that the learning horizon may have an effect consistent with Proposition 4.…”
Section: Heterogeneous Alliance Formationmentioning
confidence: 97%